Traumatic Injuries Detected during Post-Mortem Slaughterhouse Inspection as Welfare Indicators in Poultry and Rabbits - Valkova, Lenka; Voslarova, Eva; Vecerek, Vladimir; Dolezelova, Petra; Zavrelova, Veronika; Weeks, Claire (Animals, 2021)
The findings of traumatic injuries during post-mortem inspection in slaughterhouses reflect the level of pre-slaughter handling of animals at the farm and during transport to the slaughterhouse. The prevalence of traumatic injuries was monitored in poultry (1,089,406,687 broiler chickens, 20,030,744 laying hens, 1,181,598 turkeys, 37,690 geese, 28,579,765 ducks) and rabbits (1,876,929) originating from farms in the Czech Republic and slaughtered in slaughterhouses in the Czech Republic between 2010 and 2019. The greatest incidence of traumatic injuries was found in laying hens (2.80%) and rabbits (1.52%); while the overall incidence of trauma was less than 0.5% in other species and categories. The results show that the current rearing conditions and/or pre-slaughter handling of poultry and rabbits particularly affect the limbs; traumatic findings were significantly (p < 0.01) more frequent on the limbs than on the trunk in all species studied. In poultry, traumatic findings on the trunk were orders of magnitude lower to negligible, so the focus should be on preventing injuries to the limbs. In rabbits, the difference was less pronounced, and many injuries were found on both limbs (0.83%) and trunk (0.69%). Our results emphasize the need to reconsider both housing and pre-slaughter handling methods to determine minimum standards for the protection of rabbits, which are still lacking in European legislation.
Keywords: duck; goose; rabbit; injury; broiler chicken; end-of-lay hen; post-mortem inspection